THE EFFECTIVENESS OF PSYCOEDUCATION APPLICATION IN ONE OF THE FAMILY MEMBERS WHO CARE FOR THE ELDERLY WITH DECREASED COGNITIVE FUNCTION IN LOWERING ANXIETY LEVELS DURING THE COVID-19 PANDEMIC IN TAMBAK ASRI VILLAGE, MALANG REGENCY - Nanik Dwi Astutik; Berliany Venny Sipollo (Jurnal Keperawatan Malang, 2022)
Background: The older adults is a group that is vulnerable to Covid-19 infection. This is due to a degenerative process that causes a decrease in the body's immunity so that the older adults are susceptible to infections, including COVID-19. In conditions like this, the older adults are easily overwhelmed by feelings of excessive anxiety which can have an impact on physical health. Purpose: Analyzing the effectiveness of the application of family psychoeducation in families who have older adults with decreased cognitive function during the COVID-19 pandemic in reducing family anxiety levels in Tambak Asri Village, Malang Regency Methods: Quasy - experiment pre-post test with control group design. Families who have older adults with decreased cognitive function will be divided into two groups, namely the control group and the intervention group. Data will be collected before and after the intervention (pre-post test with control group design), sampling technique using random sampling. There was 20 older adults and data analysis using t-test. Result: The average anxiety of families with older adults who experienced decreased cognitive function in the intervention group before the intervention was 69.9 (moderate anxiety), while in the control group 69.7 (moderate anxiety). The average anxiety of families with the older adults experiencing decreased cognitive function in the intervention group after the intervention was 51.7 (mild anxiety), while the control group was 66.9 (moderate anxiety). Conclusion: Family psychoeducation is effective in reducing the anxiety of families who have elderly who experience cognitive decline during the Covid-19 pandemic based on the Paired Samples Test and T-Test statistical tests with p-value = 0.000 and Mann-Whitney test p-value = 0.000..